An enhanced adaptive duty cycle scheme for optimum data transmission in wireless sensor network - Mohd Fadzil, Abdul Kadir; Ahmad Faisal Amri, Abidin@Bharun; Zahrahtul Amani, Zakaria; Mohamad Afendee, Mohamed; Nor Surayati, Mohamad Usop (2020)
In wireless sensor network (WSN), energy efficiency is the most fundamental issue that requires special attention during the design of communication protocols. Energy waste is largely contributed by collision, idle listening, overhearing and over-emitting that occur at medium access control layer. One of the most widely used mechanism energy saving in WSN, specifically at MAC layer is Duty Cycle. Duty Cycling coordinates the sleep/wake-up time sensor nodes to maximize the network lifetime while achieving specific application goals such as high throughput or low latency. Most existing works focused more on static duty cycling which cannot guarantee the desire end-to-end delay at varying network condition. In applications with specific delay requirement, the duty cycling of every node should be adjusted separately ay runtime depending on the network conditions to achieve desired delay guarantees and energy efficiency. Recently, a few adaptive duty cycle schemes were introduced. Although energy consumption has been reduced by some degree, it leaves an open ended to the degradation of quality of service. In this research, we find the optimum data transmission in WSN. We purpose a variant of an adaptive duty cycle scheme for MAC protocol. By adaptive, these factors determine the duration of node’s listen period for various packet transmission scenarios and requirements. This result in less waiting time for each packet to be transferred as well as reduce the retransmission of undelivered packets. We anticipate this proposed method will improve the energy consumption and QoS of each node and thus the WSN. The success of this project will be contributed to the performance improvement and cost-effective sensing device.